2014
DOI: 10.4149/neo_2014_056
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of microRNA-17-92 cluster associates with tumor progression and prognosis in osteosarcoma

Abstract: MicroRNA -17-92 (miR-17-92) cluster has been demonstrated to play a crucial role in various human cancers. However, its effects in osteosarcoma have not yet been elucidated. The purpose of this study was to investigate the clinical significance of miR-17-92 cluster in osteosarcoma. MiR-17-92 cluster expression in osteosarcoma clinical samples and cell lines was detected by real-time quantitative RT-PCR. Then, the association of miR-17-92 cluster level with survival of osteosarcoma patients was performed by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 30 publications
1
21
0
1
Order By: Relevance
“…Among the target miRNAs, miR-18a-5p was selected as the study object, based on its biological function in various cancers [19,20]. miR-18a-5p, Cellular Physiology and Biochemistry a member of the miR-17-92 cluster, has been reported to be upregulated, and functions as an oncogene in OS progression [25][26][27]. We further confirmed by luciferase reporter assay and qRT-PCR, that FER1L4 interacts directly with miR-18a-5p, both in OS cell lines as well as in tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Among the target miRNAs, miR-18a-5p was selected as the study object, based on its biological function in various cancers [19,20]. miR-18a-5p, Cellular Physiology and Biochemistry a member of the miR-17-92 cluster, has been reported to be upregulated, and functions as an oncogene in OS progression [25][26][27]. We further confirmed by luciferase reporter assay and qRT-PCR, that FER1L4 interacts directly with miR-18a-5p, both in OS cell lines as well as in tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that PTEN is a target gene of miR-17 and its expression appears to be inversely correlated with miR-17 expression levels in OS tissues (27,28). In the present study, PTEN expression was significantly decreased in human OS tissues compared with in matched normal tissues (P<0.01), indicating that downregulation of PTEN may have a significant role in OS development and progression (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…DHA supplementation has been previously shown to inhibit cancer cell adhesion, proliferation and invasiveness (38, 40). We propose the basic concept that in cancer cells, disease progression involves changes in actin binding protein-mediated actin dynamic which facilitates metastasis and increases cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-17~92, a cluster of six microRNAs encoded by a single transcript, is highly expressed in malignant tumors and may function as an oncogene by negatively regulating tumor suppressor genes and/or genes that control cell proliferation, differentiation, or apoptosis (3638). Of relevance, ABPs like profilin 1 and cofilin 1 are among the predicted targets of miR~17–92 (predicted by Target Scan).…”
Section: Introductionmentioning
confidence: 99%